A Multi-Faceted Antimicrobial Stewardship Program (ASP) Intervention Using Clinical Pharmacists Reduces Antibiotic Use and Hospital-Acquired Clostridium difficile Infection (HA-CDI). (4th October 2017) - Boyd, Anthony M; Nagel, Jerod; Eschenauer, Gregory; Marshall, Vincent D; Gandhi, Tejal; Chenoweth, Carol; Petty, Lindsay; McClung, Daniel; Patel, Twisha S
Abstract: Background: ASPs continue to investigate novel ways to improve appropriate antibiotic utilization. The impact of an ASP-led, multi-faceted coaching and real-time feedback model directed towards clinical pharmacists was evaluated. Methods: A single-center, pre-post quasi-experimental study was conducted with a four-month historical control period (11/2016–2/2017) and four-month intervention period (4/2016–7/2016) to reduce the use of ceftriaxone, fluoroquinolones, and clindamycin. Clinical pharmacists were responsible for ensuring the appropriate use of these restricted antimicrobials with limited guidance by the ASP in the historical control period. The intervention was multi-faceted: ASP pharmacists provided daily coaching and feedback on use of targeted agents to the clinical pharmacists, clinical pharmacists made recommendations to optimize therapy, and in-person monthly sessions were held where a dashboard consisting of aggregated utilization data and HA-CDI rates was discussed by the ASP pharmacist. Segmented regression analysis was used to determine the significance of this intervention on the utilization of the antibiotics, measured by days of therapy (DOT) per 1000 patient-days (PD). Rates of HA-CDI were also compared between the groups. Results: The use of fluoroquinolones (34.4 vs. 26.2 DOT/1000 PD; Δ -23.9%), ceftriaxone (17.7 vs.. 13.6 DOT/1000 PD; ∆ -23.2%), and clindamycin (18.7 vs.. 13.3 DOT/1000 PD; ∆ -28.9%) decreased during the intervention period. Using segmented regression analysis, a significant decreasing rate of antibiotic use of all three agents was observed during the intervention period (Table). A significant decreasing rate of HA-CDI was also seen (rate ratio (RR): 0.787, 95% CI: 0.743–0.833, P < 0.001). Conclusion: A multi-faceted coaching and feedback intervention targeting clinical pharmacists with substantial ASP oversight can significantly reduce inappropriate antibiotic use and HA-CDI in a large hospital. Disclosures: G. Eschenauer, Merck: Grant Investigator, Research grant; V. D. Marshall, Merck: Grant Investigator, Research grant